Gingivitis- and periodontitis-associated microbiota in bovine deciduous incisor teeth – A preliminary study - Vaccari, Juliana [UNESP]; Borsanelli, Ana C.; Athayde, Flávia R.F. [UNESP]; Saraiva, Júlia R. [UNESP]; Ramos, Thamiris N.M. [UNESP]; Dutra, Iveraldo S. [UNESP] (Elsevier, 2025)
As ruminants are frequently affected by periodontal diseases, understanding their microbial communities is crucial. In this pilot study, we analyzed subgingival biofilm samples of young cattle across different states: clinically healthy (n = 5), gingivitis (n = 5), and periodontitis (n = 5) using 16S rRNA gene sequencing and co-occurrence network analysis. The findings revealed that Proteobacteria was the predominant phylum across all conditions, with Fusobacteriota constituting 27.6 % of the microbiota in periodontitis-affected sites. In healthy sites, Moraxella (21.11 %), Neisseria (13.16 %), and Lautropia (7.69 %) were the predominant genera; in gingivitis-affected sites, the leading genera were Neisseria (23.65 %), Moraxella (18.95 %), and Conchiformibius (10.79 %); and in periodontitis sites, Caviibacter (19.78 %), Moraxella (16.13 %), and Fusobacterium (7.56 %) were most prevalent. Richness and dissimilarity analyses did not show significant differences across the clinical states, but differences were found between gingivitis and periodontitis sites (p = 0.01) in diversity. The co-occurrence networks highlighted significant variances in the central phyla across the phenotypes, with a higher number of positive interactions observed in periodontitis-affected sites. Consequently, this study demonstrated that the microbiota associated with periodontitis in young cattle exhibits greater diversity compared to gingivitis. Notably, in the deciduous dentition of cattle, the genera Caviibacter and Moraxella are pivotal in the context of periodontitis and periodontal health, respectively.
Keywords: Cattle; Gingivitis; Microbiota; Periodontitis; Primary dentition